Concepts and experimental protocols towards a molecular level understanding of the mechanical properties of glassy, cross-linked proteins: Application to wheat gluten bioplastics. (March 2017) - Jansens, Koen J.A.; Telen, Lien; Bruyninckx, Kevin; Vo Hong, Nhan; Gebremeskel, Abrehet F.; Brijs, Kristof; Verpoest, Ignace; Smet, Mario; Delcour, Jan A.; Goderis, Bart
Graphical abstract: Highlights: Compression molding gluten proteins with low moisture results in glassy materials. The mechanical performance of glassy polymers is linked to the molecular properties. Experimental outcomes deviate from predictions based on theoretical concepts. Both the degree and type of cross-linking depended on the protein composition. Disulfide cross-links may contribute less to material toughness than other bonds. Abstract: Linking the mechanical performance of glassy polymeric materials to their molecular characteristics is a major challenge, even more so when proteinaceous raw materials are used with a complex cross-linking chemistry and composition dependent molecular interactions. Here, wheat gluten was separated into gliadin-rich and glutenin-rich fractions. Blends prepared thereof were compression molded (130–150 °C, 5–28 min) into glassy, brittle materials. Molecular characteristics as well as mechanical properties in bending and compression modes were determined and their mutual relations extensively discussed. The compression data were used to qualitatively predict the flexural strength values. Experimental outcomes deviated from the predictions possibly because of stress concentrating contaminants in glutenin-rich and molecular network interruptions in gliadin-rich materials. Depending on molding conditions and protein composition either only disulfide bonds or also non-disulfide cross-links were present. It is suggested that disulfide based cross-links contribute less to material toughness than other types of covalent cross-links.